Повышение экономичности и экологической эффективности теплоутилизационной системы конденсационного типа путем ввода влаги в топку котла - Ефимов, Александр Вячеславович; Гончаренко, Александр Леонидович (НТУ "ХПИ", 2017)
С целью повышения экономичности и экологических показателей системы для глубокой утилизации теплоты уходящих газов котельного агрегата небольшой паропроизводительности предложено осуществить ввод влаги в топку котла. С помощью компьютерной программы выполнено расчетное исследование по оценке влияния этой технологии на технико-экономические, теплотехнические и конструктивные характеристики теплоутилизационной системы и ее элементов. Осуществлена оценка воздействия впрыска влаги на степень снижения выбросов оксидов азота в окружающую среду. Показано, что предлагаемая технология является достаточно эффективной: при вводе 10 % влаги в зону горения топлива КПД системы повышается на 1,1 %, а концентрация оксидов азота в продуктах сгорания топлива уменьшается на 25 %.

To increase the effectiveness and ecological indices of the system used for the deep recovery of the heat of exhaust gases of the boiler unit with a low steam capacity we proposed to inject moisture into the boiler furnace. This technology is relatively inexpensive, because the pipelines of a large diameter are not required. This technology can be highly efficient for the systems of a condensation type, because the heat loss with exhaust gasses is not increased in them. Due to an increase in the amount of heat released during the condensation of excess water steam added by gasses escaping from the boiler the efficiency factor of the system or the flow rate of heated up water and condensate can also be increased. This fact is proved by the computational investigation carried out to estimatethe effect of this technology on engineering and economical performances and also on heat-engineering and structural characteristics of the heat recovery system and its elements using the computer program. The injection of 10 % of the moisture into the fuel burning zone results in the increase of the efficiency factor of the system by 1.1 % and the flow rate of the water heated for the hot water supply system is increased by 0.0679 kg/s (244 kg/h) and the condensate flow rate is increased by 0,00405 kg/s (14,6 kg/h). The temperature of heated water is increased by 1.9 °С. The estimation of the influence of the injected moisture on the level of a decrease in the emission of nitrogen oxides into the environment done using the well –known methods showed that the proposed technology is also rather efficient from the standpoint of improved ecological indices, in particular the nitrogen oxide concentration in fuel burning products has decreased by 25% with the injection of 10% of the moisture into the combustion zone.
Increasing the effectiveness and the ecologic efficiency of the heat recovery system of a condensation type by injecting moisture into the boiler furnace
Keywords: коэффициент полезного действия; расход воды; расход конденсата; площадь поверхности теплообмена; концентрация оксидов азота; efficiency factor; heated water flow rate; conden-sate flow rate; nitrogen oxide concentration